A parallel finite-element approach to CSEM forward modeling problems - Puzyrev, Volodymyr; Koldan, J.; De La Puente, J.; Cela, J. (2013)
The marine controlled-source electromagnetic method is a standard geophysical exploration tool in the offshore environment. We present a nodal finite-element method for 3D electromagnetic forward modeling with potentials. A numerical example illustrates the agreement between our method and the results of other authors. A realistic synthetic test case shows the possibilities of the finite-element method in handling completely unstructured tetrahedral meshes that allow an accurate representation of geological and bathymetric complexity, as well as anisotropy and large conductivity contrasts. Due to the usage of parallel Krylov subspace solvers and efficient preconditioners the code displays very good convergence and scalability. This method will be the basis for large scale 3D electromagnetic inversion.